Emerging roles of RNA methylation modifications in environmental metalloid or metal pollutants toxicity - Rongxian Li; Yuan Zhao; Jiao Dai; Nan Zhang; Jiamin Yuan; De Liu; Zuoshun He; Jie Yang; Shiyan Gu (Ecotoxicology and Environmental Safety)
The common environmental metalloid or metal pollutants such as arsenic, cadmium, chromium, lead, aluminum, cobalt and manganese have increasingly significant impacts on public health. They have been confirmed to be enriched step by step through the food chain to display serious toxic effects on multiple organs and tissues. Recently, emerging studies have indicated that RNA methylation modification plays essential roles in various organs and tissue toxicity under the treatment of environmental metalloid or metal pollutants. In this review, the roles and mechanisms of major RNA methylation modifications such as N6-methyladenosine (m6A), 5-methylcytosine (m5C), N1-methyladenosine (m1A) and 7-methylguanine (m7G) in the regulation of multiple organs and tissues toxic damage caused by environmental metalloid or metal pollutants are summarized. Additionally, we explore potential avenues for future investigation within the realm of RNA methylation as it pertains to the toxicity of environmental metalloid or metal pollutants. The insights presented herein are intended to offer critical research leads and a scientific foundation for the mitigation and advancement of strategies addressing the toxicity of environmental metalloid or metal pollutants.